Wanted: pediatric nephrologists! — why trainees are not choosing pediatric nephrology. (September 2014) - Ferris, Maria; Iglesia, Edward; Ko, Zion; Amamoo, Ahinee; Mahan, John; Desai, Tejas; Gibson, Keisha; Jhaveri, Kenar; Primack, William
Abstract A workforce crisis for many pediatric specialties, particularly nephrology, is due to growing retirement rates, attrition during training, and retention difficulties. To obtain specific information regarding pediatric nephrology trainee shortages, we administered two cross-sectional surveys to non-renal pediatric subspecialty fellows and pediatric nephrology program directors. We characterized the fellows' experiences with nephrology and the program directors' experiences with their fellows as well as their outcomes in the last 10 years. We analyzed responses from 531 non-renal fellows (14.4% response rate). Overall, 317 (60%) fellows rated nephrology as difficult, particularly women (65.4% vs. 49.5%, p < 0.001), with American women medical graduates rating nephrology as more difficult compared to all others (p = 0.001). More men than women (24% vs. 8%, p < 0.001) considered the monetary benefit as not adequate. Program directors (25; 64% response rate) represented 57% of all USA fellows in training, and 15 (60%) found it difficult to recruit qualified applicants. Of the 183 graduates in the past 10 years, 35 (19%) were reported as not in the USA pediatric nephrology workforce. These findings support our belief that a strong effort needs to be made by the academic community to teach nephrology in more interesting and understandable formats. While these are national samples, we were unable to contact non-nephrology fellows directly and program directors from larger programs were underrepresented. Difficulties in attracting/retaining trainees (particularly women) to nephrology must be addressed systematically, identifying incentives to practice in this field. Bold concerted efforts are required and we propose seven steps to achieve this goal.